Psychopathological factors and personality dimensions on dysfunctional eating behaviors in a sample of individuals with obesity - Attanasio, Margherita; Giuliani, Antonio; Romano, Lucia; Laidò, Cristina; Di Poggiovalle, Gilda; Le Donne, Ilenia; Di Fonzo, Valentina; Tiberti, Sergio; Valenti, Marco; Mazza, Monica (Frontiers in Psychology, 2023)
Introduction Obesity and eating disorders are considered to be part of a broad spectrum of disorders associated with weight issues and maladaptive eating styles. Several studies show that psychopathological and personality characteristics contribute to the development and maintenance of obesity and dysfunctional eating behaviors, showing a bidirectional relationship. The purpose of this study was to understand the role of psychopathological factors and personality dimensions on dysfunctional eating behaviors in a sample of individuals with obesity. Methods The study was conducted with 96 individuals with obesity (31 males and 65 females) who underwent psychological assessment. The instruments administered included the Cognitive Behavioral Assessment 2.0 - Primary Scales, the Minnesota Multiphasic Personality Inventory-2, and the Eating Disorder Inventory. Relationships between dysfunctional eating behaviors and personality and psychopathological factors were explored through mediation analysis. Results and discussion Our results showed that difficulties related to impulse control and behavior, along with negative and dysphoric emotions, may be associated with difficulties in eating behavior. Mediation analysis showed that the combination of depressive and obsessive-compulsive symptomatology may exacerbate or contribute to the occurrence of eating disorders. These psychopathological aspects should be taken into account during the assessment of patients who decide to undergo bariatric surgery and should be targets of specific psychological interventions.